Subdural grid implantation for intracranial EEG recording: CT and MR appearance. - Silberbusch, M A; Rothman, M I; Bergey, G K; Zoarski, G H; Zagardo, M T (American Journal of Neuroradiology, 1998)
PURPOSE Subdural grid arrays are used when seizure activity cannot be located by ictal scalp recordings and when functional cortical mapping is required before surgery. This study was performed to determine and compare the CT and MR imaging appearance of subdural EEG grids and to identify the types and frequency of associated complications.METHODS We retrospectively reviewed the medical records and imaging studies of 51 consecutive patients who underwent 54 craniotomies for subdural EEG grid implantation with either stainless steel or platinum alloy contacts between June 1988 and September 1993. Twenty-two patients had both CT and MR examinations, 27 patients had CT only, and five patients had MR imaging only. All studies were assessed for image quality and degradation by the implanted EEG grids, for intra- and extraaxial collections, and for mass effect, with differences of opinion resolved by consensus.RESULTS Subdural EEG grids caused extensive streak artifacts on all CT scans (corresponding directly to grid composition) and mild to moderate magnetic susceptibility artifacts on MR images. Sixteen associated complications were detected among the 54 patients imaged, including four significant extraaxial hematomas, four subfalcine or transtentorial herniations, two tension pneumocephali, two extraaxial CSF collections, two intraparenchymal hemorrhages, and one case each of cerebritis and brain abscess. In all but four cases, the detected complications were not clinically apparent and did not require specific treatment. There were no residual sequelae.CONCLUSION Because of extensive streak artifacts, CT showed only gross complications, such as herniation and grid displacement by extraaxial collections. MR imaging artifacts were more localized, allowing superior evaluation of subdural EEG grid placement and associated complications.